Dr. Ulvi Hasanov — Deep Plane Facelift — Baku - Hasanov, Ulvi (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ulvi Hasanov, practicing in Baku, Azerbaijan. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003260; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; azerbaijan; baku